Reduced biophotonic activities and spectral blueshift in Alzheimer’s disease and vascular dementia models with cognitive impairment - Wang, Zhuo; Xu, Zhipeng; Luo, Yi; Peng, Sisi; Song, Hao; Li, Tian; Zheng, Jiaxin; Liu, Na; Wu, Shenjia; Zhang, Junxia; Zhang, Lei; Hu, Yuan; et al. (Frontiers in Aging Neuroscience, 2023)
Background Although clinically, Alzheimer’s disease (AD) and vascular dementia (VaD) are the two major types of dementia, it is unclear whether the biophotonic activities associated with cognitive impairments in these diseases share common pathological features. Methods We used the ultraweak biophoton imaging system (UBIS) and synaptosomes prepared by modified percoll method to directly evaluate the functional changes in synapses and neural circuits in AD and VaD model animals. Results We found that biophotonic activities induced by glutamate were significantly reduced and spectral blueshifted in synaptosomes and brain slices. These changes could be partially reversed by pre-perfusion of the ifenprodil, a specific antagonist of the GluN2B subunit of N-methyl-D-aspartate receptors (NMDARs). Conclusion Our findings suggest that AD and VaD pathology present similar but complex changes in biophotonic activities and transmission at synapses and neural circuits, implying that communications and information processing of biophotonic signals in the brain are crucial for advanced cognitive functions.